Kidding pattern and mortality rate of indigenous local goat kids reared under semi-intensive system in Andaman and Nicobar Islands - PERUMAL, P; KUNDU, A; SUNDER, J; KUNDU, M S; BHATTACHARYA, D; SUJATHA, T; DE, A K (The Indian Journal of Animal Sciences, 2019)
Data of 544 kids born during 2000 to 2017 maintained at the institute were analysed to study the factors affecting the sex ratio and mortality rate in Andaman local goat under semi-intensive system. Frequency and percentage of kidding and mortality rate of kids under different years (2000 to 2017), months (January to December) and seasons (wet and dry season) were calculated. Relative female ratio (RFR) as well as secondary sex ratio (SSR) was also calculated to assess the sex ratio of the kids in the organised goat farm. Result revealed that birth rate, sex ratio, mortality rate, kidding pattern such as singles, twins and triplets varied with months, seasons and years. Birth rate, mortality rate, single and twine birth were higher in monsoon than dry season whereas triplets, quadruplet and sex ratio were higher in dry season than monsoon. In conclusion, sex ratio, birth rate and mortality rate differed significantly between months/seasons/years and wet season/months were most conducive for breeding of goat under semi-intensive system in Andaman and Nicobar Islands.